Radiation target: Moving from theory to practice - Qian Li; Guoping Zhao; Wei Han; Shengmin Xu; Lijun Wu (Nuclear Analysis)
Radiation target theory refers to that ionizing radiation hits specific molecules or organellaes in cells, resulting in structural damage, gene mutation, chromosome breakage and other target effects of biological macromolecules. It is the most widely accepted theory in radiobiology, radiotherapy and radiation protection. Based on this theory, several different mathematical models have been proposed to evaluate the cell killing effect in radiotherapy and radiation risk assessment. In addition, the target(s)-related technologies have also been well developed. Here, we review the development of radiation target theory and mathematical models, focusing on the related researches on three key biological radiation targets: DNA, protein and lipid. Alternatively, improvements in physical radiation technology based on radiation targets and developments in biotechnology (e.g., omics analysis, chromatin conformation analysis, and the application of organoid models) are described. This review provides insights for a better understanding of the roles of targeting effects in radiobiology, and emphasizes the application value of target-related techniques in clinical treatment.